Integrasi Kearifan Lokal dalam Reboisasi Hutan Lindung Batukliang Utara - Isfana, Qaila; Ayuni, Firda; Iskandar, Junaidi (Lembaga Publikasi Ilmiah Nusantara, 2025)
Reforestation of protected forests is a vital effort in maintaining environmental sustainability and preventing ecosystem degradation. This study aims to analyze the role of local wisdom in supporting reforestation programs in the North Batukliang Protected Forest area, Central Lombok Regency. The method used is a descriptive qualitative approach through field observations, in-depth interviews with traditional leaders, local communities, and relevant agencies, as well as document analysis. The results of the study show that the local community possesses traditional values that support forest conservation, such as the